Kontekstualisasi Pesan Moral Kisah Aṣḥāb Al-Jannah Surat Al-Qalam Ayat 17-33 - Hesty Kusuma Waty; Masruchin; Abuzar Al-Ghifari (Program Pascasarjana IIQ Jakarta, 2024)
This study aims to identify the moral massage found in the narrative of Aṣḥāb Al-Jannah (the people of the garden) contained in Surah Al-Qalam (68) verses 17-33 as well as forms of contextualization in the current context. This study belongs to the library research category and employs a descriptive-analytical method. This study indicates that the first describes the socio-historical of Surah Al-Qalam verses 17–33, which is the Qur'anic reactions to the circumstances of Arab society in the past. The narrative tells the story of Abu Jahal and the people of Makkah who denied the mercies of Allah. The second movement involves contextualizing Surah Al-Qalam verses 17-33, resulting in aspects of moral ideal values. The ideal values are, first, the value of monotheism (always remembering Allah in all matters). The second ideal value is spiritual value (implementing zakat in life). The third ideal value is the social value (guiding on virtue). Third, social value (guiding on virtue), character value of human responsibility, character building (endeavor, optimism, prayer, and tawakal or reliance on God), avoiding selfishness and materialism, imitating the good nature of parents, egalitarianism, and self-control (repentance and devotion to Allah).